Simulation analysis on the effect of inlet channel bed slope and diameter of basin for water vortex turbine system - Alfera Yap (2022)
Hydropower is one of the renewable energies that generate electricity. One of the micro hydropower systems is the Gravitational Water Vortex Power Plant (GWVPP) which is a cost-effective and environmentally friendly energy system that uses a gravity vortex pool to convert low-head potential energy into kinetic energy that drives turbines. Some researchers have made different analyses on different configurations of the water vortex turbine system. However, there is still little research related to the inlet channel bed slope and the size of the diameter of the basin. Thus, this project will focus on the study of the effects of these two different configurations. Nevertheless, this study will study more on hydraulic energy which studies the effects on the stability and uniformity of the vortex profile formation with a diffuser and without a turbine. In this study, the use of Computer-Aided Design (CAD) by using SolidWorks 2018 software and Computational Fluid Dynamics (CFD) by using the ANSYS CFX R21 software was utilized. The reliability of this software was validated by experimental work which the percentage of difference is 9.09%. The inlet channel bed slope was investigated from without a slope and up to six degrees of slope, while the diameter of the basin was investigated from 0.30m to as large as 0.60m diameter of basin. The simulation results show different effects for both configurations. It was found that the inlet channel bed slope does not affect the water vortex system, but the change of size for the diameter of the basin shows different effects and the preferable result will be based on a different type of data obtained.